2013
DOI: 10.1002/nha3.20031
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and enculturation of older students returning to a traditional university

Abstract: As baby boomers approach the age of retirement, they are increasingly returning to higher education to pursue degrees for encore careers. Academic planners must pay careful attention to the specific concerns of this population to help ease their transition to a university setting after decades of absence. This qualitative study investigated the meaning of the experiences of seven students participating in a 62‐and‐over reduced tuition program at a large, traditional Southeastern university. Two sets of semi‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…In the recent decades higher education institutions in most industrialized societies have thus witnessed a steady increase in the proportion of ''older'' mature students (e.g., students who have worked professionally and who choose to return to university in pursuit of additional degrees or personal development, European Commission 2013; Donaldson and Townsend 2007;Taylor and House 2010). The issues what institutional policy and practice can do to make it more likely that mature individuals will enroll in higher education, and how they can effectively support those who get enrolled are hot topics in recent higher education research (Howard and Davies 2013;Mathers and Parry 2010;Parks et al 2013;Stoessel et al 2014;Villar et al 2011). One important issue in this context revolves around overcoming ageism.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the recent decades higher education institutions in most industrialized societies have thus witnessed a steady increase in the proportion of ''older'' mature students (e.g., students who have worked professionally and who choose to return to university in pursuit of additional degrees or personal development, European Commission 2013; Donaldson and Townsend 2007;Taylor and House 2010). The issues what institutional policy and practice can do to make it more likely that mature individuals will enroll in higher education, and how they can effectively support those who get enrolled are hot topics in recent higher education research (Howard and Davies 2013;Mathers and Parry 2010;Parks et al 2013;Stoessel et al 2014;Villar et al 2011). One important issue in this context revolves around overcoming ageism.…”
Section: Introductionmentioning
confidence: 97%
“…Not surprisingly, several pieces of empirical evidence exist that suggest that older mature students may anticipate (or actually face) prejudice and social isolation from traditional younger students because of their age (e.g. Findsen 2012; Parks et al 2013;Peterson and Bryant 1999;Wurtele and Maruyama 2013). From the perspective of our theoretical model outlined above, emphasizing age diversity on university websites should signal to potential applicants that the university has committed to creating a learning environment that fosters mutual respect for and among all students independent of their age (and perhaps also irrespective of other minority group characteristics).…”
Section: Introductionmentioning
confidence: 98%
“…Establish a dedicated library staff member who acts as an advocate/representative for non-traditional students (Parks et al, 2013).…”
Section: Recommendationsmentioning
confidence: 99%
“…non-traditional student orientation, transfer students) to promote library resources and services (Parks et al, 2013;MacKenzie, 2007).…”
Section: Recommendationsmentioning
confidence: 99%
“…Research in the area of adult students and higher education is well-established in Europe, the United Kingdom, the United States, and Australia. A consideration of adult learner identities (Brine & Waller, 2007;Crossan, Field, Gallacher, & Merrill, 2003;Kasworm, 2005Kasworm, , 2010 including their perceived separation from younger students, isolation and relational dynamics (Baxter & Britton, 2011;Mallman & Lee, 2016Parks, Evans, & Getch, 2013;Simi & Matusitz, 2016) reveals the complexity of being an adult learner in higher education. Research findings have also suggested that adult learners struggle with social constructions (Massey, 2015;Parks, Evans, & Getch, 2013;Simi & Matusitz, 2016), particularly in navigating the academic culture and social dynamics of university or college, while studies focusing on student anxiety, such as mentor and targeted induction programs, demonstrate the types of resources and university services which have an impact on a successful adjustment (Burton, Golding Lloyd, & Griffiths, 2011).…”
Section: Introductionmentioning
confidence: 99%